ANALISIS PENGARUH PENDEKATAN PEMBELAJARAN TEACHING AT THE RIGHT LEVEL (TARL) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIQIH - Andi Wahyumulianti; Sri Mulianah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The Teaching at the Right Level (TaRL) approach is a learning strategy that adapts the learning process to students’ actual abilities rather than their grade levels. This study aims to determine the correlation between the implementation of the TaRL approach and the improvement of student learning outcomes in the subject of Fiqh at MAN Pinrang. This research is a quantitative study using a quasi-experimental method with a pre-test–post-test design. The study involved 36 eleventh-grade students as research subjects. The research instrument consisted of a test administered before and after the intervention. Data were analyzed using the paired sample t-test to assess the significance of learning outcome improvements. The results showed a significant positive correlation between the implementation of the TaRL approach and students’ learning achievements. This was indicated by the post-test average score of 83.67, which was higher than the pre-test average of 55.39, with a significance level of p = 0.000 < 0.05. These findings suggest that the TaRL approach is an effective solution to address student learning disparities and improve the quality of Fiqh instruction.